2020
DOI: 10.1177/2050312120921273
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided drainage of difficult-to-access liver abscesses

Abstract: Objectives: Antibiotic therapy and percutaneous drainage have been the first-line treatments for liver abscesses. However, percutaneous drainage of abscesses may be challenging in difficult-to-access locations such as the caudate lobe. The aim of this review was to determine the indications, technical feasibility and efficacy of endoscopic ultrasound-guided drainage of difficult-to-access liver abscesses. Methods: A literature review of original articles, abstracts, case series and case reports describing endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Another case report also concluded similar success of EUS-AD with SEMS in liver abscess located in the right liver lobe [ 59 ]. Recently, a review by Chin et al from 15 studies demonstrated 97.5% technical success rate and 95% clinical success rate without any major complications (5% complication due to stent migration) of EUS-AD procedure [ 60 ].…”
Section: Potential Use Of Interventional Eus In Other Liver Conditions (Ascites; Liver Abscess)mentioning
confidence: 99%
“…Another case report also concluded similar success of EUS-AD with SEMS in liver abscess located in the right liver lobe [ 59 ]. Recently, a review by Chin et al from 15 studies demonstrated 97.5% technical success rate and 95% clinical success rate without any major complications (5% complication due to stent migration) of EUS-AD procedure [ 60 ].…”
Section: Potential Use Of Interventional Eus In Other Liver Conditions (Ascites; Liver Abscess)mentioning
confidence: 99%
“…The poblem with plastic stents is inadequate drainage. Although FCSEMS provides good drainage, it is not cost effective and has a risk of severe complications like stent migration, perforation and bleeding 10 11 .…”
Section: Discussionmentioning
confidence: 99%
“…CT or USG-guided percutaneous drainage is commonly used, but surgical drainage (either open or laparoscopic) is also used in select cases. Endoscopic USG-guided drainage is a new technique that has been shown to be safe and effective in difficult-to-access liver abscesses 49…”
Section: Liver Abscessmentioning
confidence: 99%